Do migrant remittances have state de-legitimizing tendencies? A micro-survey based evidence from Africa - Abreham Adera (Cogent Economics & Finance, 2023)
This paper examines the micro-level link between migrant remittances and state legitimacy. The paper argues that there are two theoretical channels through which remittances may ultimately erode state legitimacy. First, remittance income earners may use remittance income to bribe state institutions, and thus may feel that they do not need to abide by the laws those state institutions enact. Second, remittances provide funds for political mobilization and thus may enhance uprisings against autocratic states. I test these claims using individual-level pooled data from 3 rounds of the Afrobarometer surveys. For the quantitative analysis, I use multiple linear regression, propensity score matching, and an informal method of testing for omitted variables bias. Overall, the findings of the study show that remittance-receiving Africans hold de-legitimizing behavior towards the state.
Keywords: 330; Africa; individuals; Legitimacy; micro analysis; remittances